Violence, abuse and the implications for mental health and wellbeing of security operatives in the United Kingdom: the invisible problem - Talas, Risto (Policing and society, 2021)
This paper addresses mental health and wellbeing among security operatives in the UK using a mixed-methods approach of survey questionnaire and interviews. The survey questionnaires were designed using three hybrid surveys: Warwick-Edinburgh Mental Wellbeing Scale; The Post-Traumatic Stress Disorder (PTSD) Checklist-Civilian Version (PCL-C); and CAGE-AID as a screen for substance misuse. The survey questionnaires were distributed with the support of the Security Industry Authority and the GMB Union and 754 completed surveys were returned and 15 interviews conducted. Results from the completed survey questionnaires show that 39.3% of the respondents were showing symptoms of PTSD and that many of the security operatives suffered varying degrees of verbal abuse and threats of physical violence with a number reporting acts of violence to themselves and other security operatives during the course of their employment. A key finding was the lack of provision of mental health and wellbeing services provided by the security companies to their employees and managers in general unable or unwilling to accept that some employees were suffering from poor mental health and wellbeing.